The Role of Mouthguards in Preventing Temporomandibular Joint Injuries During Contact Sports: A Prospective Study - Ravalika Singarapu; Elavenil Panneerselvam; Sasikala Balasubramaniam; Komagan Prabhu Nakkeeran; Mrunalini Ramanathan; Krishnakumar Raja V B (Frontiers in Dentistry, 2023)
Objectives: Injuries to the maxillofacial region during contact sports is a well-known issue. Protective measures have been advised to prevent and reduce these problems. Awareness regarding the role of mouthguards in preventing temporomandibular joint (TMJ) injuries during contact sports, is limited. The aim of the present study was to assess awareness regarding the use of mouthguards during contact sports and incidence of TMJ injuries in sportspersons.